Gestational Vitamin D Supplementation Leads to Reduced Perinatal RXRA DNA Methylation: Results From the MAVIDOS Trial. (18th January 2019) - Curtis, Elizabeth M; Krstic, Nevena; Cook, Eloïse; D'Angelo, Stefania; Crozier, Sarah R; Moon, Rebecca J; Murray, Robert; Garratt, Emma; Costello, Paula; Cleal, Jane; Ashley, Brogan; Bishop, Nicholas J; et al.
ABSTRACT: We have previously demonstrated inverse associations between maternal 25(OH)‐vitamin D status and perinatal DNA methylation at the retinoid‐X‐receptor‐alpha (RXRA) locus and between RXRA methylation and offspring bone mass. In this study, we used an existing randomized trial to test the hypothesis that maternal gestational vitamin D supplementation would lead to reduced perinatal RXRA locus DNA methylation. The Maternal Vitamin D Osteoporosis Study (MAVIDOS) was a multicenter, double‐blind, randomized, placebo‐controlled trial of 1000 IU/day cholecalciferol or matched placebo from 14 weeks' gestation until delivery. Umbilical cord (fetal) tissue was collected at birth and frozen at −80°C ( n  = 453). Pyrosequencing was used to undertake DNA methylation analysis at 10 CpG sites within the RXRA locus (identified previously). T tests were used to assess differences between treatment groups in methylation at the three most representative CpG sites. Overall, methylation levels were significantly lower in the umbilical cord from offspring of cholecalciferol‐supplemented mothers, reaching statistical significance at four CpG sites, represented by CpG5: mean difference in % methylation between the supplemented and placebo groups was −1.98% (95% CI, −3.65 to −0.32, p  = 0.02). ENCODE (Encyclopedia of DNA Elements) evidence supports the functionality of this locus with strong DNase hypersensitivity and enhancer chromatin within biologically relevant cell types including osteoblasts. Enrichment of the enhancer‐related H3K4me1 histone mark is also seen in this region, as are binding sites for a range of transcription factors with roles in cell proliferation, response to stress, and growth factors. Our findings are consistent with previous observational results and provide new evidence that maternal gestational supplementation with cholecalciferol leads to altered perinatal epigenetic marking, informing mechanistic understanding of early life mechanisms related to maternal vitamin D status, epigenetic marks, and bone development. © 2018 The Authors. Journal of Bone and Mineral Research Published by Wiley Periodicals Inc.